Internalisasi Nilai-nilai Religi pada Usia Dini dalam Menyongsong Generasi Emas yang Islami (Taallum: Jurnal Pendidikan Islam, 2017)
The successful of a religious personality is through the childs learning needs to be supported by the exemplary elements from both teachers and parents. For the purpose of the implementation can be done in a gradual learning strategies and develop habituation program or daily activities. To implement the program of religious values, teachers must be constantly creative and innovating to use a variety of approaches in accordance with the level of development and students needs, a comprehensive curriculum, and the continuity between the development program with other programs. The presence of the curriculum in 2013 with a science characteristic (observe, ask, explore, associate, communicate) and authentic assessment have to be understood early childhood teachers so that the internalization of religious values ââcan be absorbed in the learning process. Each children must has expected to be a good boy who obey the religious values. Early Childhood Education as an institution that expectedly nurturing children in a golden age.